Analisis Faktor-Faktor yang Mempengaruhi Keputusan Investasi Pelaku UMKM Di Kudus - faridhatun faidah (Jurnal Ekonomi dan Bisnis, 2020)
The purpose of this study is to examine the factors that influence the investment decisions of SMEs entrepreneurs in Kudus, which consist of financial literacy, demographic factors and risk tolerance. This study uses primary data from a sample of 80 entrepreneurs chosen randomly in Kudus Regency. The research method uses multiple regression analysis with the help of the SPSS 23. The results of this study indicate that financial literacy has a significant positive effect on the investment decisions of SMEs entrepreneurs in Kudus. Meanwhile demographic and risk tolerance factors do not have a significant influence on investment decisions.